Effects of volume rate and spray pressure of an air-assisted sprayer on pesticide distribution and drift on pear prees - Magdalena, Jorge Carlos; Benitez Piccini, Jose Edgardo; Di Prinzio, Alcides Pascual; Behmer, Sergio Néstor; Villarroel, Luis Santiago; Gabbanelli, Matias Sebastian; Daga, Gabriel Antonino (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010